2007
DOI: 10.1108/17465729200700011
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the evidence on the effect of the built and physical environment on mental health

Abstract: This paper assesses the strength of the evidence on the impact of the physical environment on mental health and well‐being. Using a systematic review methodology, quantitative and qualitative evaluative studies of the effect of the physical environment on child and adult mental health published in English between January 1990 and September 2005 were sought from citation databases. The physical environment was defined in terms of built or natural elements of residential or neighbourhood environments; mental hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 97 publications
(160 reference statements)
5
103
0
Order By: Relevance
“…Furthermore, urban settings not only determine PA but also psychological wellbeing and mental health (Fujiwara and Kawachi, 2008;Clark et al, 2007). Studies have demonstrated how mental health depends heavily on social capital (Bowling and Stafford, 2007) and resources that individuals can access through their networks (Fujiwara and Kawachi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, urban settings not only determine PA but also psychological wellbeing and mental health (Fujiwara and Kawachi, 2008;Clark et al, 2007). Studies have demonstrated how mental health depends heavily on social capital (Bowling and Stafford, 2007) and resources that individuals can access through their networks (Fujiwara and Kawachi, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…3,7,29 But none of the work has been conducted among a pregnant population. While prior work is suggestive, most has estimated the built environment using census data, 23 has not focused on psychosocial status, 3,7,17,22 and has considered a limited range of psychosocial attributes. In an effort to address these limitations, this paper will assess the relationship between the urban built environment and maternal psychosocial status using directly observed neighborhood characteristics and a wide range of psychosocial attributes.…”
mentioning
confidence: 99%
“…But more commonly researchers have concluded that research methodologies, sampling, instruments of measurement or proxies, and/or the underlying questions are not yet sufficiently specified or suitable (Newman, 2001;Thomson et al, 2001;Weich, 2005;Whitley et al, 2005;Clark et al, 2007).…”
Section: The Challenge Of Social Complexitymentioning
confidence: 99%